Relationship of Noise Levels with Hypertension in Textile Workers in Semarang City - Intan Sekar Arumdani; Onny Setiani; Tri Joko; Mursid Raharjo; Sakundarno Adi (Universitas Diponegoro, 2022)
Noise is associated with a risk factor for several cardiovascular diseases, one of which is hypertension. Hypertension is estimated to cause 7,5 million deaths, or about 12.8% worldwide. The textile industry is exposed to high noise intensity because it constantly uses machines. The results of a preliminary study of noise measurement showed that the average at 6 points reached 90 dBA. The Threshold Value for the noise level contained in permitted government regulation is ≤ 85 dBA for duration of exposure of 8 hours. The measurement results exceed the threshold value. This study was analytical observational research with a Cross-sectional study design. The sample in this study was 74 workers textile industry in Semarang city. The average noise intensity measurement in the entire machine area of spinning unit 5 of the Semarang City Textile Industry is 87.49 dBA. Based on statistical test analysis, the results of noise levels (p-value = 0.037), working period (p-value = 0.015), and continuity of use of ear protection equipment (p-value = 0.048) and duration of exposure per day (p-value 0.510) were obtained. There is a significant relationship between noise level, working period, and continuity of Ear Protection Equipment use with the incidence of hypertension.